Present energy scenario and solar energy as an alternative option for environmental protection - Mishra, Dilip; Saikhedkar, N K (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> In today’s scenario utilization of energy in an effective manner is must and that is the need of the time. After industrial revolution we are using the classical energy sources which are dependent on fossil fuels. The rate of exploration ofthese resources are much higher along with the higher rate of pollution. With the advancement in technology more efficient alternative energy sources have been recognized for environmental protection and are now available for various applications. This paper focuses one of the alternativeused for energy generation i.e. the solar option. In this study comparison of flat plate solar collector and evacuated tube solar collector is carried out and feasibility is reported. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->